212k views
2 votes
Simplify the expression below.

4x(3x − 7) − 19x2

User Aluxian
by
5.4k points

2 Answers

2 votes

Assuming you meant 19×2


4x(3x − 7) − 19×2 = 12
x^(2)-28x-38


If not just reply

User Dennis Ninj
by
5.6k points
3 votes

Answer: The required simplified form is
-7x^2-28x.

Step-by-step explanation: We are given to simplify the following expression :


E=4x(3x-7)-19x^2~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

We will try to simplify the bracket first an then will combine the terms as much as possible.

From (i), we have


E\\\\=4x(3x-7)-19x^2\\\\=12x^2-28x-19x^2\\\\=-7x^2-28x.

Thus, the required simplified form is
-7x^2-28x.

User Chad Edrupt
by
4.5k points